2015
DOI: 10.1002/chem.201501782
|View full text |Cite
|
Sign up to set email alerts
|

Iodine(III)‐Mediated Diazidation and Azido‐oxyamination of Enamides

Abstract: In this study we demonstrate that the combination of bis(tert-butylcarbonyloxy)iodobenzene and lithium azide in acetonitrile allows the diazidation of various enamide substrates. The azido-oxyamination of the same substrates can be carried out in the presence of 2,2,6,6-tetramethylpiperidine N-oxide (TEMPO). Control experiments strongly suggest that this latter process occurs through a shift in nature of the in situ generated electrophilic species from a radical to a cation. Finally, the versatility of the nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 68 publications
1
19
0
Order By: Relevance
“…Xu and co‐workers developed an iron(II)‐catalyzed diastereoselective diazidation method for non‐functionalized and highly functionalized olefins . Interesting developments have also been described by the groups of Loh and Dodd in the copper‐catalyzed oxyazidation and diazidation of styrene derivatives. Despite extensive research and significant advances in this field, however, the stereoselective metal‐catalyzed introduction of an azido group into organic compounds remains challenging.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Xu and co‐workers developed an iron(II)‐catalyzed diastereoselective diazidation method for non‐functionalized and highly functionalized olefins . Interesting developments have also been described by the groups of Loh and Dodd in the copper‐catalyzed oxyazidation and diazidation of styrene derivatives. Despite extensive research and significant advances in this field, however, the stereoselective metal‐catalyzed introduction of an azido group into organic compounds remains challenging.…”
Section: Methodsmentioning
confidence: 99%
“…Metal-catalyzed azidation has emerged therefore as as traightforward and atom-economic strategyt oi nstallv arious nitrogen-based motifs. [9] Interesting developments have also been described by the groupso fL oh [10] and Dodd [11] in the copper-catalyzed oxyazidation and diazidation of styrene derivatives. [6] In 2013, radical azidooxygenationo fv ariouss tyrene derivatives ands pecifically of electron-rich alkenes was achieved by Studerw ith an excellent diastereoselectivity in presenceo fN 3 -iodine(III) and TEMPO-Na.…”
mentioning
confidence: 99%
“…Preliminary mechanistic studies have revealed that the reaction proceeds via in situ-generated chlorinated hypervalent iodine species (Scheme 28b) [95]. As an extension of this protocol, a pseudohalide source and TEMPO ((2,2,6,6-Tetramethylpiperidin-1-yl)oxyl) combination resulted in the oxyazidation reaction (Scheme 28c,d) [96].…”
Section: Alkene Oxyfunctionalizationmentioning
confidence: 99%
“…Lastly, in a series of three publications, Dodd and co‐workers demonstrated the versatility of the reaction of PIDA with disubstituted enamides (Scheme ) . They were able to access α‐halo and α‐azide aminals by performing the reaction in ethanol.…”
Section: Enamine and Enamide Substratesmentioning
confidence: 99%